Blockchain Applications in Supply Chain Transactions - Christian F. Durach; Till Blesik; Maximilian von Düring; Markus Bick (Journal of Business Logistics, 2021)
Blockchains, a disruptive technology with potentially many applications in modern-day supply chain (SC) transactions, have not been adequately reflected by theory. Researchers and business managers must understand where and when blockchains' application may be expected and investigated. The present study clarifies the discussion about blockchain application areas (BAAs) in SC transactions and their relevance for businesses. This study combines the findings from three methodological approaches: an extant literature review, a Delphi study, and a survey of 151 German machinery and equipment sector business managers. The results further our understanding of blockchains' business opportunities among SC transactions and verify and extend Iansiti and Lakhani's (Harvard Business Review 2017; 95: 118) blockchain adoption framework. Verified customer reviews and product quality certification are identified as the most relevant blockchain usages in SC transactions. Interestingly, we anticipate the least likely adoption of blockchains to occur for document-signing processes despite arguments within the literature that suggest otherwise. Two newly identified BAAs—logistics and delivery systems—and token-curated registries rank among the top four most relevant. The present study's valuation of BAAs advances theory and will likely affect business strategies by indicating where, when, and why businesses should participate in blockchain networks.
Keywords: 650; blockchain applications; digitalisation; digital; supply chain; Delphi study; survey